A review on the role of dispersion and receptor models in asthma research. (15th October 2021) - de Ferreyro Monticelli, Davi; Santos, Jane Meri; Goulart, Elisa Valentim; Mill, José Geraldo; Kumar, Prashant; Reis Jr., Neyval Costa
Abstract: There is substantial evidence that air pollution exposure is associated with asthma prevalence that affects millions of people worldwide. Air pollutant exposure can be determined using dispersion models and refined with receptor models. Dispersion models offer the advantage of giving spatially distributed outdoor pollutants concentration while the receptor models offer the source apportionment of specific chemical species. However, the use of dispersion and/or receptor models in asthma research requires a multidisciplinary approach, involving experts on air quality and respiratory diseases. Here, we provide a literature review on the role of dispersion and receptor models in air pollution and asthma research, their limitations, gaps and the way forward. We found that the methodologies used to incorporate atmospheric dispersion and receptor models in human health studies may vary considerably, and several of the studies overlook features such as indoor air pollution, model validation and subject pathway between indoor spaces. Studies also show contrasting results of relative risk or odds ratio for a health outcome, even using similar methodologies. Dispersion models are mostly used to estimate air pollution levels outside the subject's home, school or workplace; however, very few studies addressed the subject's routines or indoor/outdoor relationships. Conversely, receptor models are employed in regions where asthma incidence/prevalence is high or where a dispersion model has been previously used for this assessment. Road traffic (vehicle exhaust) and NOx are found to be the most targeted source and pollutant, respectively. Other key findings were the absence of a standard indicator, shortage of studies addressing VOC and UFP, and the shift toward chemical speciation of exposure. Graphical abstract: Image 1 Highlights: More asthma studies using dispersion/receptor models for VOC exposure are needed Receptor models were used in regions of high asthma prevalence Traffic is the most targeted source in asthma studies using dispersion models Similar methodologies give contrasting risks between air pollution and asthma Receptor and dispersion models coupling were not explored at its full potential Abstract : Studies display contrasting results of the association between air pollution and an asthma-related outcome, even using similar methodologies.